Analisis Tingkat Kepadatan Timbunan Batu Menggunakan Pengujian Water Replacement di Ruas Tol Probowangi Paket 3B - Rahmasari, Fernanda; Pratama, Satria Apta Mozza; Fauzan, Sayed Ahmad; Syifa, Faluth (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
This study evaluates the compaction level of mountain-excavated rock fill used as subgrade material on the Probolinggo–Banyuwangi Toll Road, package 3B (STA 23+925–STA 25+550), using the water replacement method. The analysis was conducted by comparing in-situ density with the maximum laboratory dry density to determine the Compaction Ratio (CR) as an indicator of compaction performance. The results from testing on 22 locations indicate CR values ranging from 101.1% to 103.9%, with an average of 102.52%, confirming that field compaction was effective, homogeneous, and exceeded the minimum Standard Proctor requirement (≥100%). The material moisture content was close to the Optimum Moisture Content (OMC), while the predominance of 50–60 cm rock sizes promoted effective particle interlocking. This condition resulted in a stable and dense subgrade with high bearing capacity under traffic loading. These findings confirm the technical feasibility of utilizing locally sourced excavated rock as subgrade fill material, providing a scientific basis for material efficiency, resource optimization, and enhanced quality of toll road construction